2010
DOI: 10.1007/s10823-010-9124-8
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging through the Eyes of Alaska Natives: Exploring Generational Differences Among Alaska Natives

Abstract: There is very little research on Alaska Native (AN) elders and how they subjectively define a successful older age. The lack of a culturally-specific definition often results in the use of a generic definition that portrays Alaska Native elders as aging less successfully than their White counterparts. However, there is a very limited understanding of a diverse array of successful aging experiences across generations. This research explores the concept of successful aging from an Alaska Native perspective, or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Qualitative studies among Alaska Natives found that successful aging was defined by participants as achieving a respected role in one’s community 22. Unsuccessful aging was defined as low activity, alcohol consumption, and loss of faith in oneself 21. Younger participants believed that their current physical health was a predictor of the ability to age successfully, whereas elders linked successful aging to the ability to maintain mental health and participate within their community 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies among Alaska Natives found that successful aging was defined by participants as achieving a respected role in one’s community 22. Unsuccessful aging was defined as low activity, alcohol consumption, and loss of faith in oneself 21. Younger participants believed that their current physical health was a predictor of the ability to age successfully, whereas elders linked successful aging to the ability to maintain mental health and participate within their community 21…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of the reviewed articles, engagement seemed to have a significant association with age,20 and in some cases, could be used to discriminate between those aging successfully and those who were not 2123. Some participants indicated that engagement was the expression of a decision to maintain involvement in activities and with others, despite the challenges of health crises 29.…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been strong appeals for developing culture-specific measurement for successful ageing (e.g. Lewis 2010;Liang and Luo 2012), to date, there are no established definitions and measurements of culture-specific successful ageing for the non-western countries in current literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, there remains a need for more research among minority elderly populations to address the needs of specific groups (Dillaway & Byrnes, 2009; Lewis, 2010). Studies from diverse Asian ethnic population groups are particularly lacking.…”
Section: Introductionmentioning
confidence: 99%